Hepatic arterial infusion chemotherapy versus systemic chemotherapy for advanced intrahepatic cholangiocarcinoma: a meta-analysis of survival outcomes - Zeng, Di; Cheng, Zhimeng; Liu, Geng; Lu, Jiong; Li, Bei (Frontiers in Immunology, 2025)
BackgroundIntrahepatic cholangiocarcinoma (iCC) is an aggressive hepatobiliary malignancy with limited therapeutic options and poor survival outcomes. Hepatic arterial infusion chemotherapy (HAIC) has emerged as a promising treatment alternative to systemic chemotherapy, but its clinical benefits require comprehensive evaluation.MethodsA systematic review and meta-analysis were conducted, including 10 studies with 1,493 patients. Data on overall survival (OS), progression-free survival (PFS), and key prognostic factors were extracted. Pooled hazard ratios (HR) were calculated using a random-effects model.ResultsHAIC significantly improved OS (HR = 0.51, p < 0.001) and PFS (HR = 0.58, p < 0.001) compared to systemic chemotherapy. Subgroup analyses revealed consistent benefits across various patient characteristics, including age, tumor stage, and baseline liver function. Patients with lower tumor burden (HR = 0.45) and ECOG performance status ≤1 (HR = 0.50) derived the greatest benefit. Additionally, patients with CA 19–9 levels <1,000 U/mL showed significantly improved OS (HR = 0.48).ConclusionHAIC prolongs survival and improves disease control in advanced iCC patients compared to systemic chemotherapy. These findings support the adoption of HAIC as a valuable treatment strategy for selected patients, particularly those with lower tumor burden and favorable performance status.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024615752.